Public performances: studies in the carnivalesque and ritualesque - Santino, Jack, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
This volume is written by scholars who have presented research at the Conference on Holidays, Ritual, Festival, Celebration, and Public Display. The papers themselves are not necessarily the same as their original presentations, and represent only a few of the authors who have presented at this annual conference over the years. This annual conference began in 1997 and the 15th was held in 2011 at the Sorbonne. This book reflects on the field of Ritual Studies, and the role and influence of the conference--Paraphrase from the introduction.
From carnivalesque to ritualesque: public ritual and the theater of the street / Jack Santino -- Locality, spectacle, state politics: the carnival traditions in fifteenth-century Nuremburg and twentieth-century Trinidad / Samuel Kinser -- Conflict display in the black Atlantic / Roger D. Abrahams -- Protesting and grieving: ritual, politics, and the effects of scale / Beverly Stoeltje -- Political percussions: Cork brass bands and the Irish evolution 1914-1922 / John Borganovo -- ¡Que bonita bandera!: place, space and identity as expressed with the Puerto Rican flag / Elena Martinez -- The lives of processions in Bali and Lambok, Indonesia / David Harnish -- The anthropology of festivals: changes in theory and practice / Laurent Sebastian Fournier -- The politics of cultural promotion: the Umtheto Festival of Malawi's Northern Ngoni / Lisa Gilman -- Music as activist spectacle: AIDS, breast cancer and LGBT choral singing / Pamela Moro -- The "Days of Scanzano": the carnivalesque and the ritualesque in an anti-nuclear protest / Dorothy Zinn -- "Some are born green, some achieve greenness ...": protest theater and environmental activism / Scott Magelssen -- The material culture of remembrance in Ireland: roadside memorials as contested spaces / Barbara Graham -- The politics of junk: social protest, "outsider" environments, and ritualesque display at the Heidelberg Project in Detroit / Daniel Wojcik.
Keywords: Annual Conference on Holidays, Ritual, Festival, Celebration and Public Display; Political customs and rites; Holidays -- Political aspects; Parades; Processions; Festivals